1996
DOI: 10.1080/01688639608408291
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Brief Measure of Semantic Priming

Abstract: Neuropsychologists use a variety of stimuli to investigate semantic memory functioning. Methodological concerns limit interpretation of performance differences between patients and nonpatient controls. The present study describes the development of a brief measure of semantic memory. Results indicate that this measure of semantic priming provides a brief, yet sensitive, measure of semantic memory. It may prove useful for researchers interested in examining semantic memory processes in cognitively impaired indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…It is not clear why there is a discrepancy between some of the previous literature (Balota & Lorch, 1986;McNamara & Altarriba, 1988;Sayette et al, 1996;Spitzer et al, 1993a,b) and this study with regard to controls and indirect priming of neutral stimuli. Only further investigation at different SOAs may elucidate the reasons for this.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…It is not clear why there is a discrepancy between some of the previous literature (Balota & Lorch, 1986;McNamara & Altarriba, 1988;Sayette et al, 1996;Spitzer et al, 1993a,b) and this study with regard to controls and indirect priming of neutral stimuli. Only further investigation at different SOAs may elucidate the reasons for this.…”
Section: Discussioncontrasting
confidence: 73%
“…These findings have been recently replicated at the short SOA (a long SOA was not studied) (Weisbrod et al, 1998), in thought disordered (TD) schizophrenics and nonthought disordered (NTD) patients and controls. However, in normal subjects word pronunciation paradigms have recorded significant priming with indirect word pairs at various SOA's (Balota & Lorch, 1986;Sayette, Hufford, & Thorson, 1996), whereas studies using lexical decision paradigms, have produced mixed findings (McKoon & Ratcliff, 1992;Shelton & Martin, 1992).…”
mentioning
confidence: 97%
“…Such indirect prime-target relationships typically give rise to significant priming effects (Kreher, Holcomb, & Kuperberg, 2006;Bennett & McEvoy, 1999;Kiefer, Weisbrod, Kern, Maier, & Spitzer, 1998;Livesay & Burgess, 1998;Weisbrod, Maier, Harig, Himmelsbach, & Spitzer, 1998;Sayette, Hufford, & Thorson, 1996;Spitzer, Braun, Maier, Hermle, & Maher, 1993;McKoon & Ratcliff, 1992;McNamara, 1992;Shelton & Martin, 1992;McNamara & Altarriba, 1988;Ratcliff & McKoon, 1988;; Motes, personal communication, for a metaanalysis; but see de Groot, 1983).…”
Section: Types Of Relationships Between Prime and Targetmentioning
confidence: 96%
“…For instance, McNamara and Altarriba (1988), McKoon and Ratcliff (1992), Sayette, Hufford, and Thorson (1996), and Livesay and Burgess (1998) all found significant mediated priming in the LDT when the stimulus list contained only mediated and unrelated items (but see Chwilla, Kolk, & Mulder, 2000, for a different finding). The use of such lists eliminates any noticeable relation between the prime and the target and presumably prevents participants from engaging in any strategic semantic matching process.…”
Section: Mediated Primingmentioning
confidence: 99%
“…Priming from these items is almost certainly automatic, since strategic mechanisms such as expectancy generation and/or semantic matching should work (and indeed have worked) against obtaining priming for these items. By carefully designing experiments to reduce or eliminate conscious strategies, Balota and Lorch (1986), McNamara and Altarriba (1988), McKoon and Ratcliff (1992), Sayette et al (1996), Livesay andBurgess (1998), and have all found significant mediated priming effects.…”
Section: Summary Of "Pure Associative" Primingmentioning
confidence: 99%